Răspuns:
-1
Explicație pas cu pas:
[tex]\sqrt{6} *(\frac{1}{\sqrt{3} } *\frac{1}{\sqrt{2} } )-\sqrt{3} *(\frac{1}{\sqrt{2} } *\frac{2}{\sqrt{6} } )-\sqrt{2} *(\frac{1}{\sqrt{6} } *\frac{3}{2\sqrt{3} } )=\\\sqrt{6} *(\frac{\sqrt{3} }{3} *\frac{\sqrt{2} }{2} )-\sqrt{3} *(\frac{\sqrt{2} }{2} *\frac{2\sqrt{6} }{6} )-\sqrt{2} *(\frac{\sqrt{6} }{6} *\frac{3\sqrt{3} }{6} )=\\\sqrt{6} *\frac{\sqrt{6} }{6} -\sqrt{3} *\frac{\sqrt{12} }{6} -\sqrt{2} *\frac{\sqrt{18} }{6} =\\\frac{6}{6} -\sqrt{3} *\frac{2\sqrt{3} }{6} -\sqrt{2} *\frac{3\sqrt{2} }{6} =\\[/tex]
1 - [tex]\frac{3}{3} -\frac{2}{2} =[/tex]
1-1-1=-1
Sper ca te-am ajutat!